2013
DOI: 10.1101/lm.027664.112
|View full text |Cite
|
Sign up to set email alerts
|

A recollection of mTOR signaling in learning and memory

Abstract: Mechanistic target of rapamcyin (mTOR) is a central player in cell growth throughout the organism. However, mTOR takes on an additional, more specialized role in the developed neuron, where it regulates the protein synthesis-dependent, plastic changes underlying learning and memory. mTOR is sequestered in two multiprotein complexes (mTORC1 and mTORC2) that have different substrate specificities, thus allowing for distinct functions at synapses. We will examine how learning activates the mTOR complexes, survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 159 publications
(194 reference statements)
4
99
0
Order By: Relevance
“…31 Transient activation of Akt/mTOR by NMDA and TrkB receptors is required for long-term potentiation of synaptic transmission, however constitutive overexpression of Akt in CA1 is detrimental to learning in rats, possibly because of loss of temporal regulation of Akt. 30,32 Akt can also modulate NMDA/TrkB receptor signaling leading to increased calcium influx after NMDA and BDNF stimulation. 33 Akt and/or mTOR might also facilitate normal learning through NMDA, AMPA, and other receptor trafficking or phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…31 Transient activation of Akt/mTOR by NMDA and TrkB receptors is required for long-term potentiation of synaptic transmission, however constitutive overexpression of Akt in CA1 is detrimental to learning in rats, possibly because of loss of temporal regulation of Akt. 30,32 Akt can also modulate NMDA/TrkB receptor signaling leading to increased calcium influx after NMDA and BDNF stimulation. 33 Akt and/or mTOR might also facilitate normal learning through NMDA, AMPA, and other receptor trafficking or phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…[83][84][85][86][87][88] All of these proteins are encoded by TOP mRNAs, 64 suggesting that mTORC1 may participate in synaptic plasticity by locally increasing the availability of translation factors and other components of the translational apparatus. 78 Evidence for this comes from the observation that TOP mRNAs are transported into dendrites and axons where they are locally translated in an mTORC1-dependent manner. 88,89 In fact, TOP mRNAs represent some of the most abundant transcripts localized within these structures.…”
Section: Local Translation Of Top Mrnas In Activitydependent Protein mentioning
confidence: 99%
“…[80][81][82] Neuronal mTORC1 becomes activated in response to different stimulation paradigms (i.e., forskolin, high-frequency stimulation, mGluR agonists), and its inhibition by rapamycin was found to block long-lasting synaptic changes and memory consolidation in different animal models. 78 Notably, a number of studies have documented an elevation in the levels of elongation factors eEF1A and eEF2, as well as ribosomal protein S6, in response to synaptic activity in both mammals and Aplysia. [83][84][85][86][87][88] All of these proteins are encoded by TOP mRNAs, 64 suggesting that mTORC1 may participate in synaptic plasticity by locally increasing the availability of translation factors and other components of the translational apparatus.…”
Section: Local Translation Of Top Mrnas In Activitydependent Protein mentioning
confidence: 99%
See 1 more Smart Citation
“…mTORC1 is a critical cellular energy and nutrient status sensor that integrates signals from multiple pathways to regulate protein, lipid, and nucleotide synthesis, and it has also been identified as an important modulator of learning and memory (Dash et al 2006;Gkogkas et al 2010;Hoeffer and Klann 2010;Graber et al 2013;Santini et al 2014). Previous studies using cultured cells deprived of serum/amino acids have shown that glutamine can either increase or decrease mTORC1 activity (Deldicque et al 2008;Nicklin et al 2009;Kim et al 2013).…”
Section: Discussionmentioning
confidence: 99%